Bidang Garapan Kesiswaan Dalam Administrasi Pendidikan - Lubis, Dicky Chandra; Jannah, Miftahul; Siregar, Nita Afriani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Educational administration plays a vital role in ensuring the effectiveness and efficiency of education. Student management, as part of educational administration, handles various aspects related to students. This article examines the concept, objectives, functions, and scope of student management. The goal is to create a learning environment that is conducive to student development. The research method used is a literature study, with data collection from various sources such as books, journals, and previous research. The results show that student management includes planning, organizing, implementing, and supervising. The scope includes the management of students, educators, curriculum, facilities and infrastructure, and administration.